VD_FINDINFO Arrêt / 2023 / 217 vom 4. April 2023 - VD Tribunal cantonal (2023)
GAIN IMMOBILIER, FORTUNE PRIVÉE ET COMMERCIALEDROIT FISCAL, COTISATION AVS/AI/APG | 9 al. 1 LAVS, 9 al. 3 LAVS, 17 RAVS, 23 al. 4 RAVS, 23 RAVS, 27 RAVS